2015
DOI: 10.1007/s11664-015-3940-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal Chalcogenide Nanocrystalline Solid Thin Films

Abstract: Over the past decades, chemical bath deposition (CBD) has proven its suitability and has established itself as one of the prominent techniques for depositing different metal chalcogenide semiconductor thin films via ion-byion or by adsorption of colloidal particles from the chemical bath on the substrate. It is a simple, cost-effective and convenient method for large-scale deposition and has recently received a surge of interest. This article reviews the research progress in various methods or techniques inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 154 publications
0
7
0
Order By: Relevance
“…Metal complexes containing organochalcogenide ligands comprise the class of compounds referred to collectively as metal chalcogenolates. These materials have applications in catalysis, electronic materials, medicine, and biomimetic chemistry. There are numerous benefits to the development of new metal chalcogenolate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes containing organochalcogenide ligands comprise the class of compounds referred to collectively as metal chalcogenolates. These materials have applications in catalysis, electronic materials, medicine, and biomimetic chemistry. There are numerous benefits to the development of new metal chalcogenolate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the various novel techniques have been established for the synthesis of nanocrystalline semiconducting metal chalcogenides including microwave-assisted heating, sol-gel method, solvothermal technique, thermal evaporation, sonochemical method, photochemical synthesis, sonoelectrochemical method, microemulsion route, electrochemical template synthesis, high-energy ball milling, sputtering, pulse laser deposition, etc. [22][23][24][25][26][27][28][29][30][31][32][33]. In the present study, nanomaterials synthesis is achieve by using melt quenching technique as this is a simplest, most cost effective as well as proven technique for producing high-quality nanomaterials along with optimum stoichiometry and morphology [5,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, nanomaterials synthesis is achieve by using melt quenching technique as this is a simplest, most cost effective as well as proven technique for producing high-quality nanomaterials along with optimum stoichiometry and morphology [5,[34][35][36][37][38]. Other researchers also reported that the progression of inclusion of Pb additives have considerable influence on the growth of nanocrystalline semiconducting chalcogenide materials [1,2,3,4,5,6,22,23,24,25,26,27,28,29,30,31,32,33,39,40,41,43]. In some cases, Pb additive act as a modifier in the host system by increasing the number of defects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the energy gap of these films lies approximately 40 eV which is very optimal for photo-conducting materials, non-linear optics, and other optoelectronic devices. Remarkably, Cd-Zn sulphide films possess a band gap between CdS (2.42 eV) and ZnS (3.66 eV) which can be tuned by varying the ratio of Cd and Zn [14]. This spectacular energy band gap of these films guided them into window absorption losses and turned out a rise in short-circuit current in the solar cell.…”
Section: Introductionmentioning
confidence: 99%